The Development of a Graduate Program in Health Information Management - Johns, M. L. (Methods of Information in Medicine, 1994)
The development of a graduate program in Health Information Management is described. The purpose of the program is to prepare individuals to assume executive level roles in a variety of health-care enterprises in health information resources management. The curriculum is based on empirical findings of a role delineation study of chief information officers (ClOs) in the USA. A model of professional practice of the CIO was developed from study findings which describes the role of the CIO from the standpoint of functional areas of entrepreneur, resource allocator, negotiator, information disseminator, information monitor, leader, and operations manager.
Keywords: Curriculum; Health Information Management; Information Officer